Calpain‐mediated cleavage of p53 in human cytomegalovirus‐infected lung fibroblasts. Issue 3 (3rd December 2018) - Chen, Zhenping; Boor, Paul J.; Finnerty, Celeste C.; Herndon, David N.; Albrecht, Thomas
Abstract: Endogenous fragments of p53 protein were identified in human cytomegalovirus (HCMV)‐infected human lung fibroblasts, particularly a 44‐kDa N‐terminal fragment [hereafter referred to as p53(ΔCp44)], generated via calpain cleavage. The fragment abundance increased in a biphasic manner, peaking at 6‐9 hours and 48 hours post infection. Treatment of LU cells with calpain inhibitors eliminated most detectable p53 fragments. In cell‐free experiments, exogenous m‐calpain cleavage generated p53(ΔCp44). Attempts to preserve p53 proteins by treating cells with the calpain inhibitor E64d for 6 hours before harvesting increased the sensitivity of p53 to calpain cleavage. p53 in mock‐infected cell lysates was much more sensitive to cleavage and degradation by exogenous calpain than that in HCMV‐infected cells. The proteasome inhibitor MG132 stabilized p53(ΔCp44), particularly in mock‐infected cells. p53(ΔCp44) appeared to be tightly associated with a chromatin‐rich fraction. The abundance of p53β was unchanged over a 96‐h time course and very similar in mock‐ and HCMV‐infected cells, making it unlikely that p53(ΔCp44) was p53β. The biological activities of this and other fragments lacking C‐terminal sequences are unknown, but deserve further investigation, given the association of p53(ΔCp44) with the chromatin‐rich (or buffer C insoluble) fraction in HCMV‐infected cells.